Early recovery of T-cell function predicts improved survival after T-cell depleted allogeneic transplant. Issue 8 (3rd August 2017) - Goldberg, Jenna D.; Zheng, Junting; Ratan, Ravin; Small, Trudy N.; Lai, Kuan-Chi; Boulad, Farid; Castro-Malaspina, Hugo; Giralt, Sergio A.; Jakubowski, Ann A.; Kernan, Nancy A.; O'Reilly, Richard J.; Papadopoulos, Esperanza B.; et al.
Abstract: Infection, relapse, and GVHD can complicate allogeneic hematopoietic stem cell transplantation (allo-HSCT). Although the effect of poor immune recovery on infection risk is well-established, there are limited data on the effect of immune reconstitution on relapse and survival, especially following T-cell depletion (TCD). To characterize the pattern of immune reconstitution in the first year after transplant and its effects on survival and relapse, we performed a retrospective study in 375 recipients of a myeloablative TCD allo-HSCT for hematologic malignancies. We noted that different subsets recover sequentially, CD8 + T cells first, followed by total CD4 + and naïve CD4 + T cells, indicating thymic recovery during the first year after HSCT. In the multivariate model, a fully HLA-matched donor and recovery of T-cell function, assessed by PHA response at 6 months, were the only factors independently associated with OS and EFS. In conclusion, T-cell recovery is an important predictor of outcome after TCD allo-HSCT.